SVM based Iris Classification - Subha, R; Pushpa Rani, M (International Journal of Computer Sciences and Engineering, 2025)
In the modern computer era, the greatest importance is given to the individuals to secure and verify. Among all other Biometric, Iris recognition is one of the best methods to provide distinctive verification for each person based on the structure of the iris. Support Vector Machines (SVMs) are generally known as an efficient supervised learning model for taxonomy problems. The success of an SVM classifier depends on its parameters as well as the structure of the data. In this paper, we present the various uses of SVM based iris classifications.